Possession title in Peruvian civil law - Lama More, Héctor Enrique (2008)
The present article is about the possession within the frame of the Peruvian civil right and focuses its attention on the possession and the roll of the title in the exercise of this real right. The right of posesion is approached from the point of view of the legal act and its effect as a cause of the possessory right, as well as the right that the law recognizes to the possessor of the good. Putative title and fair title, interversion of the title of possession, mediate and immediate possession, legitimate and illegitimate possession, precarious possession constitute subjects that are disussed in this article.